Hollywood musicals - Cohan, Steven, 1948- (London ; New York : Routledge, 2020)
"Hollywood Musicals offers an insightful account of a genre that was once a mainstay of 20th century film production and continues to draw audiences today. What is a film musical? How do musicals work, formally and culturally? Why have they endured since the introduction of sound in the late 1920s? How are they more than glittery surfaces or escapist fare? Highlights include extended discussions of such celebrated musicals from the studio era as The Love Parade, Top Hat, Holiday Inn, Stormy Weather, The Gang's All Here, Meet Me in St. Louis, Cover Girl, Mother Wore Tights, Singin' in the Rain, Gentlemen Prefer Blondes, The Band Wagon, Seven Brides for Seven Brothers, and Jailhouse Rock as well as later films, such as Cabaret, All that Jazz, Beauty and the Beast, and La La Land."--
Defining the Musical -- A Brief Account of the Long History of the Hollywood Musical -- Analyzing Musicals -- Stars of the Classic Musical -- Five Auteur Directors.
SIBF2023
P.B
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Musical films -- United States -- History and criticism